Composition-dependent electrocatalytic activities of NiFe-based selenides for the oxygen evolution reaction. (20th November 2018) - Xuan, Cuijuan; Xia, Kedong; Lei, Wen; Xia, Weiwei; Xiao, Weiping; Chen, Lingxuan; Xin, Huolin L.; Wang, Deli
Abstract: Exploring low-cost and high-efficient electrocatalysts for oxygen evolution reaction (OER) is still an ongoing challenge to substitute noble metal materials. In this work, NiFe-based selenide (Ni-Fe-Se) is synthesized by hydrothermal treatment of metal-organic frameworks (MOFs) and Se powder. The effects of hydrothermal temperature and mass ratio of precursors on the decomposition and selenization of MOFs were investigated. Compared with NiFe based oxide, Ni-Fe-Se is favorable for improving the electronic conductivity and reduce the charge transfer resistance, promoting the formation of the higher oxidative valence of Ni species during OER process. Benefiting from the desirable advantages with unique composition, the Ni-Fe-Se material prepared under optimal conditions shows excellent electrocatalytic activities toward OER with the lower overpotential of 216 mV at a current density of 10 mA cm −2 . Besides, the resulting Ni-Fe-Se catalyst exhibits excellent durability when used as air cathode in Zn-air battery. Graphical abstract: Ni-Fe-Se nanomaterials synthesized with MOFs as precursors exhibit unique composition of NiSe2 and NiFe2 Se4, and show better OER electrocatalytic activities compared with Ni-Fe-O and outstanding stability in Zn-air battery. Highlights: NiFe-based selenide (Ni-Fe-Se) is synthesized with MOFs as precursors. The relationship between composition and electrocatalytic activity is investigated. The optimal Ni-Fe-Se shows enhanced OER catalytic activities compared with Ni-Fe-O. The optimal Ni-Fe-Se shows good stability when used as air cathode in Zn-air battery.